BASICS: farmers to pay money to get quality seed - Hemant Nitturkar - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Hemant Nitturkar, Head, BASIC project in an interview at BASICS ARPM 2017